Soil macrofauna and leaf functional traits drive the decomposition of secondary metabolites in leaf litter. (August 2019) - Ristok, Christian; Leppert, Katrin N.; Scherer-Lorenzen, Michael; Niklaus, Pascal A.; Bruelheide, Helge
Abstract: Leaf litter decomposition is closely linked to soil nutrient cycling. Both vary with environmental conditions, leaf litter diversity, faunal decomposer community and leaf litter chemistry. Polyphenols, i.e. phenolics and tannins, are important secondary metabolites in leaf litter and are considered a major impediment to whole-leaf decomposition. While the function of polyphenols is well studied, the mechanisms and drivers of their decomposition are largely unknown. We reasoned that polyphenol decomposition is driven by the same factors as whole-leaf decomposition. We hypothesized that polyphenol decomposition rates increase with leaf litter richness, decrease with macrofauna exclusion and are related to traits characterizing leaf litter quality. We measured decomposition rates of polyphenols in leaf litter of seven subtropical Chinese tree species, sampled at five dates and in a fully factorial design that manipulated litter richness and macrofauna access. We further estimated leaf carbon and nitrogen contents and leaf toughness using near-infrared spectroscopy. We showed that 1) phenolics and tannin decomposition rates did not depend on leaf litter species richness, 2) the decomposition rates of phenolics and tannins were up to one magnitude higher than whole-leaf decomposition rates, 3) the exclusion of macrofauna increased phenolics and tannin decomposition rates, 4) the leaf nitrogen content positively affected the phenolics decomposition rates and 5) the tannin-to-nitrogen ratio was the best predictor of whole-leaf decomposition. We conclude that the fast decomposition of phenolics and tannins in the early stages of whole-leaf litter decomposition is an essential ecological process. Low molecular weight phenolics that enter the soil can accelerate microbial growth, while potentially toxic tannins leave the leaf tissue, and thus, enable the consecutive whole-leaf decomposition. Our study is the first to show that macrofauna occurrence negatively affects the decomposition of ecological relevant secondary plant metabolites. This points to the importance of considering biotic interactions between different trophic levels to fully understand the mechanisms of leaf litter decomposition. Highlights: Litter species identity rather than litter diversity drives polyphenol decomposition. Soil macrofauna negatively affects the decomposition of secondary plant metabolites. Leaf nitrogen content positively affects the phenolics decomposition rates. Tannin-to-nitrogen ratio is best predictor of whole-leaf decomposition.